Dengue in End Stage Renal Disease Patients – A Case Series from a Tertiary Renal Centre of Bangladesh - Jabin, Masrura; Mostafi, Mamun; Shahriar, Ahmed; Alamgir, Saad Bin; Chowdhury, Tanvir; Billah, Mst. Arifa; Nusrat, Nahida; Roy, Shatabdi; Rahman, Shuhanur; Sarwer, Golam; et al. (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Abstract not available J Bangladesh Coll Phys Surg 2023; 41: 92-95